Implementasi Rancangan Meja untuk Produksi Emping Garut - Luddy Indra Purnama; Deny Ratna Yuniarta; Luciana Triani Dewi (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2023)
Arrowroot chips are among the best goods in the province of the Special Region of Yogyakarta. The issue is the craftspeople's complaints about producing arrowroot chips, particularly the pounding procedure. Inappropriate and persistent working positions throughout the pounding process lead to employee health issues and may further lower productivity. This service aims to implement work environments, namely designing work tables to manufacture arrowroot chips. The design of the manufacturing table is decided upon through a democratic approach. While creating the production table, ergonomics is used. The final task in the community service projects for arrowroot chip artisans is the design of a manufacturing table, testing its functionality, and teaching others how to maintain one.